Evaluating the US pharmaceutical patent policy - Olena Izhak; Tanja Saxell; Tuomas Takalo (Bank of Finland, 2021)
The debate on whether COVID-19 vaccine patents are slowing down the pace of vaccination and the recovery from the crisis has brought the optimal design of pharmaceutical patent policy to the fore. In this paper we evaluate patent policy in the US pharmaceutical industry. We estimate the effect of patent length and scope on generic entry prior to the expiration of new drug patents using two quasi-experimental approaches: one based on changes in patent laws and another on the allocation of patent applications to examiners. We find that extending effective patent length increases generic entry whereas broadening protection reduces it. To assess the welfare effects of patent policy, we match these empirical results with a model of new drug development, generic entry, and patent length and scope. Optimal policy calls for shorter but broader pharmaceutical patents.
URN:NBN:fi:bof-202112302177
Keywords: I18; K20; L13; O34; O31; 330; Patent policy; pharmaceuticals; generic entry; innovation; imitation